The impact of innovation on exports of Vietnamese manufacturing and processing enterprises: the moderating role of environmental uncertainty - Hue Thi Hoang; Ngan Hoang Vu; Hang Thu Nguyen; Hanh Thi Hai Nguyen; Bao Quoc Mai (Cogent Business & Management, 2024)
This study investigates the impact of innovation dimensions on the export activities of Vietnamese manufacturing and processing enterprises, considering the moderating role of environmental uncertainty. By applying the Probit Effect Random Regulatory Model (RE Probit) and xtTobit, the study utilizes three different sources of secondary data in the period 2016–2019: the General Statistics Office (GSO)'s annual enterprise census, the Survey on the use of technology in the production of manufacturing and processing companies by GSO, and the Provincial Competitiveness Index (PCI) of the Vietnam Chamber of Commerce and Industry (VCCI) to determine the correlation between the research variables. The research findings demonstrate that innovation positively affects both the propensity and intensity of exports. Specifically, when compared to non-innovative firms, those that prioritize innovation observe a notable 12.4% increase in export propensity and a 1.4% enhancement in export intensity. Moreover, the study highlights the moderating role of environmental uncertainty, encompassing challenges related to basic infrastructure, transport infrastructure, communication infrastructure, and institutional environment, in mitigating the impact of innovation on export outcomes. These results provide a comprehensive understanding of how process and product innovation affect export propensity and intensity while considering the complexities introduced by environmental uncertainty. Consequently, the study offers several implications that can aid policymakers in enhancing export performance, particularly in dynamic and changing environments.This research investigates the impact of innovation on the exports of Vietnamese manufacturing and processing enterprises, specifically looking at how environmental uncertainty moderates this relationship. Innovation is a notable driver of economic growth and development and affects the ability to compete in global markets, especially for firms in Vietnam - an emerging economies country with various changes. Therefore, by examining the moderating role of environmental uncertainty, the study broadens our understanding of the conditions under which innovation is most effective in boosting exports. The findings of this research are important for policymakers, business leaders, and anyone interested in understanding how innovation can contribute to the growth and success of businesses in Vietnam and other emerging economies.
Keywords: 650; Innovation; export; environmental uncertainty; manufacturing and processing enterprises; Vietnam